A comparative study of the relationship between circular economy, economic growth, and oil price across South Asian countries - Apostu, Simona Andreea; Hussain, Anwar; Kijkasiwat, Ploypailin; Vasa, Laszlo (Frontiers in Environmental Science, 2022)
This study investigates the relationship between economic growth, oil price, and circular economy through biomass energy consumption in South Asian countries, examining the possibility of biomass consumption by enhancing economic growth and decreasing oil price. Energy is the backbone of economic growth, while biomass energy resources being the best renewable energy resource alternative considering the production cost. There are no studies in the literature with regard to the influence of biomass consumption on economic growth and oil price; our study has been designed to fill this gap. For this, we used data for the period 2010–2020 and ARDL and Granger causality. The findings show that all elasticities are statistically significant in the short term for Pakistan, India, Bangladesh, and Sri Lanka. In the long term, coefficients of oil price for Pakistan and Sri Lanka are positively associated with significant elasticities, whereas biomass energy consumption is negatively associated with oil price in India and Bangladesh. Biomass energy consumption significantly impacts the economic growth of Pakistan and Bangladesh in the long term, whereas in the case of India and Bangladesh, an association between biomass energy consumption and GDP is shown. As a policy implication, governments can create and adjust policies in order to reduce costs in the energy system and protect the environment from pollution with the adoption of a biomass energy system because fossil oil and coal energy systems are unfavorable to economic growth, especially across South Asian countries.